Sejarah Kuliner Baytat (Anak Gandum): Akulturasi dan Adaptasi Budaya Kuliner Eropa dalam Masyarakat Melayu Bengkulu 1685–2025 - Mohammad Akbar; Siti Fatimah (Jurusan Sejarah FIS UNP, 2026)
This study examines the history and origins of Baytat (Anak Gandum) as an aristocratic food within the Malay community of Bengkulu during the period 1685–2025. It aims to trace the emergence of Baytat, its historical development, and the role of society in shaping Baytat as a high-status culinary tradition. The research employs a historical method with a qualitative approach, including the stages of heuristics, source criticism, interpretation, and historiography. The findings indicate that Baytat emerged during the British colonial period through interactions between the Bengkulu community and Europeans, who introduced wheat flour, baking techniques, and new patterns of food presentation and consumption. In British tradition, cakes were typically served in large portions and sliced, while in Dutch tradition smaller cakes were developed for individual consumption. These influences contributed to the formation of Baytat’s characteristics. At that time, the ingredients used were considered expensive and were therefore accessible only to the aristocracy, making Baytat a high-status food. The Malay community of Bengkulu subsequently preserved and imbued Baytat with social meaning as a symbol of honor and social status. Over time, Baytat became part of broader community traditions while continuing to retain its historical and symbolic values.